On the Construction of Benefit Coordination Mechanism of Dairy Supply Chain in China - Teng Fei, Cuixia Li (Forest Chemicals Review)
There is a conflict between the maximization of supply chain interests and their own interests, which makes the dairy supply chain unable to achieve the maximum synergy and affects its market competitiveness. Therefore, scholars pay more and more attention to how to maintain the stable and efficient operation of dairy supply chain and improve its market competitiveness through more reasonable benefit distribution. This paper studies the problem of benefit distribution from the perspective of coordination. Taking the dairy supply chain as the research object, this paper constructs the relationship model between benefit distribution, risk sharing, trust, information sharing and supply chain benefit coordination. The influence of benefit distribution and risk sharing on supply chain benefit coordination is discussed, with emphasis on the influence of benefit distribution on supply chain benefit coordination; The influence of trust among supply chain members on supply chain benefit coordination is discussed; The influence of supply chain members; information sharing on supply chain benefit coordination is discussed. According to the theoretical model, empirical research, scale design and data collection are carried out. SPSS17. 0 combined with reliability calculation and lisre l8. 7 statistical software are used for reliability analysis, validity analysis and structural equation model test analysis to verify whether the hypothesis relationship is tenable. According to the verification results, this paper puts forward corresponding suggestions on the construction of benefit coordination mechanism of dairy supply chain in China.